Bio-efficacy of Novel Acaricides against Bean Spider Mite, Tetranychus ludeni Zacher on Cowpea, (Vigna unguiculata L.) - Prasanthi, Singampalli; Balraj, G.; Devi, Dharanikota Lalithambica; Zeba, Arshi; Quadri, Sajiya; Prasad, Surendra (International Journal of Economic Plants, 2026)
A Field experiment was conducted during summer (April–July), 2024 at vegetable research farm, Hi-Tech Horticulture, RPCAU, Pusa to evaluate bio-efficacy and economics of new generation acaricides against cowpea bean spider mite, Tetranychus ludeni. The experiment was organized using Randomized Block Design with seven treatments including an untreated control, replicated three times. Two foliar sprays were applied 15days after infestation reaching economic threshold level, recorded mite population density one day prior to spraying, 1, 3, 7 and 14 days after each spray application. The results after the first spray indicated that Abamectin 1.9 EC had the greatest efficacy mean (9.29 mites leaf-1) followed by Fenpyroximate 5 EC (11.08 mites leaf-1) and Bifenazate 50 WP (12.62 mites leaf-1) compared to the untreated control (44.93 mites leaf-1). Similar results were observed after the second spray application, as Abamectin 1.9 EC showed the maximum efficacy with a mean mite count of 0.64 mites leaf-1 followed by Fenpyroximate 5 EC (2.49 mites leaf-1) and Bifenazate 50 WP (2.69 mites leaf-1). In case of yield and B:C ratio, Abamectin 1.9 EC recorded the highest pod yield and B:C ratio (13.013 t ha-1 & 4.75:1 respectively). This was followed by Fenpyroximate 5 EC (12.234 t ha-1 & 4.05:1) and Bifenazate 50 WP (11.587 t ha-1 & 3.94:1), Propargite 57 EC (107.48 t ha-1 and 3.84:1 ), Chlorfenapyr 10 SC (10.126 t ha-1 and 3.38:1), Hexythiazox 5.45 EC (9.280 t ha-1 and 3.20:1) compared to untreated control (7.733 t ha-1 and 2.71:1).